Efeito do extrato de Stemodia marítima Linn. na modulação da reabsorção óssea inflamatória e estresse oxidativo em um modelo de periodontite experimental em ratas - Teixeira, Alrieta Henrique (2017)
This research investigated the efficacy and toxicity of Stemodia maritima Linn. (S. maritima) extract in a model of ligature-induced periodontitis in female Wistar rats. Experimental periodontitis was induced by placing a sterilized nylon (3-0) thread around the cervix of the upper left 2 nd molar in animals of vehicle group (saline associated with the diluent dimethylsulfoxide - DMSO) and those of three other groups, with different concentrations of the S. maritime extract (Sm0.2, Sm1 and Sm5 mg / kg) which received the respective solutions via gavage for 11 days. Animals of naive group (control) were not submitted to any surgical manipulation. After this period, the animals were euthanized, the maxillae were removed for morphometric and histological analyzes (H&E). Gingival tissues were dissected for cytokine (TNF-α, IL1-ȕ, IL-8/CINC-1 and IL-10), enzymes superoxide dismutase (SOD) and catalase (CAT) dosages and gene expression by qRT-PCR of markers of inflammation and bone metabolism (TNF-α, IL1-ȕ, RANK e iNOS). Systemic parameters were analyzed as the weight variation, serum levels of hepatic enzymes (aspartate aminotransferase –AST and alanine aminotransferase –ALT), creatinine, total alkaline phosphatase (TALP), and bone alkaline phosphatase (BALP).We also performed the histological analyses of stomach, liver, kidney and heart. Parametric data were evaluated using the analysis of variance (ANOVA) and Tukey or Games-Howell multiple comparisons tests. For non-parametric data, the results were expressed as median and evaluated by the Kruskall-Wallis test followed by the Dunn's test. S. maritima5mg/kg reduced (p <0.05) alveolar bone loss, TNF-α andCINC-1 when compared to the vehicle group (p <0.05). IL-1 showed a tendency to reduce, but did not obtain statistical values.Levels of IL-10, SOD and CAT enzymes levels and also the variation of BALP increased in S. maritima 5mg/kg group in relation to the vehicle group (p <0.05). Histologically, S. maritima 5mg/kg preserved periodontal structures demonstrating the protective effect of the tissues of bone support and also reduced the gene expression of TNF-α, IL1-ȕ, RANK and iNOS. Weight variation, AST, ALT, creatinine and TALP presented p> 0.05 between groups. The results indicated that S. maritima5mg/kg had a protective effect on experimental periodontitis due to the inhibition of inflammatory parameters, alveolar bone loss and oxidative stress markers, representing a therapeutic option in the preclinical periodontitis in rats.